The use of a collaborative math tutoring model to improve content knowledge among special education teacher candidates. Issue 3 (27th May 2018) - Watt, Sarah J.; Wasburn-Moses, Leah
ABSTRACT: The mathematics achievement gap in special education is a chronic and significant challenge for the field. The need for improved teacher preparation in mathematics is crucial in addressing this gap. This study examines a capstone experience in higher level mathematics tutoring for preservice teachers. Results indicate that the experience was effective at improving preservice teachers' higher level math content knowledge compared to teachers who did not receive experiential math learning in their teacher preparation. Implications for preservice teacher preparation programs are presented.